NUMERICAL ANALYSIS OF IRREGULAR-SHAPED FLOATING BREAKWATER - Mahmuddin, Faizal (JURNAL RISET TEKNOLOGI KELAUTAN, 2012)
It is known that the floating type of breakwater is more preferable than conventional or fixed-type one especially by considering its economical and technical benefits. However, the common shape of a floating breakwater, which is usually simply a rectangular shape, could only attenuate waves in a limited range of frequency especially in short wavelength region. In longer wavelength region, it will just move following the seawater motions as a small object. In order to address this problem, an irregular-shaped floating breakwater, which utilizes the relative motion of water inside its body, which as a result could attenuate incoming waves in relatively longer wavelength region, needs to be implemented. By analyzing the relation of hydro dynamical and geometrical influences to the performance, the optimal shape and dimension can be obtained. The performance of the models described by performance index (PI) for clear and convenient comparison and assessment. The analysis and numerical computations based on the potential flow theory.